Phytochemical investigation of Cannabis sativa: Isolation and structure determination of spiroindans - Nalli, Yedukondalu; Komal; Boccia, Eleonora; Lauro, Gianluigi; Bifulco, Giuseppe; Krishna, Gamidi Rama (Journal of Molecular Structure, 2025)
Four undescribed, beta-, alpha-chevicospiranol (1, 2), 4-prenylspirenone B (3), and, 6-prenylspirenone B (4), along with ten known spiroindans were discovered in Cannabis sativa. The structures were determined through 1D, 2D NMR, HRMS, and quantum mechanical calculations. Compounds 1 and 2 have an unprecedented fused system of 3hydroxychavicol with beta- and alpha-cannabispiranol core, respectively, while 3 and 4 are prenylated spiroindan congeners. Detailed NMR data assignments of isomeric pairs 2a - 2b, 3a - 3b, and 4a - 4b, corrected the misidentification of the previously reported spiroindane, prenylspirodinone (5). Besides, the crystal structures of 2a, 3a, and 5a were determined by SC-XRD experiments.
Keywords: Cannabaceae; Cannabis sativa L.; Crystal structure analysis of spiro-indans; Indian cannabis variety; NMR data of spiro-indans; Spiro-indans